From Social Media To E-Commerce: The Legal Implications Of Minister Of Trade Regulation Number 31 Of 2023 On The Separation Of Social Media And E-Commerce - Komalasari, Komalasari; Ningrum, Maya Puspita; Roza, Ahmad Fadhly; Zebua, Yefita (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
TikTok Shop is a clear example of the convergence trend between social media and e-commerce into a social commerce phenomenon, where social media platforms integrate e-commerce functions seamlessly, allowing users to interact socially and conduct transactions or conduct Trading Through Electronic Systems (PMSE) in one application. This phenomenon not only changes the way people shop but also poses new challenges in the aspects of regulation and business competition. There is a significant gap between das soll (should) and das sein (reality) in the regulation of e-commerce in Indonesia. Regulation of the Minister of Trade Number 31 of 2023 concerning Business Licensing, Advertising, Guidance, and Supervision of Business Actors in E-Commerce is a reflection of the government's efforts to improve the gap in e-commerce governance. TikTok Shop in Indonesia was officially deactivated on October 04, 2023, but on Harbolnas December 12, 2023, TikTok Shop returned with a merger with Tokopedia as a juridical implication of Trade Number 31 of 2023